A New 1, 3, 4‐Oxadiazole‐Based Hole‐Transport Material for Efficient CH3NH3PbBr3 Perovskite Solar Cells. Issue 7 (16th February 2016) - Carli, Stefano; Baena, Juan Pablo Correa; Marianetti, Giulia; Marchetti, Nicola; Lessi, Marco; Abate, Antonio; Caramori, Stefano; Grätzel, Michael; Bellina, Fabio; Bignozzi, Carlo Alberto; Hagfeldt, Anders
Abstract: A new hole‐transport material (HTM) based on the 1, 3, 4‐oxadiazole moiety (H1) was prepared through a single‐step synthetic pathway starting from commercially available products. Thanks to a deep HOMO level, H1 was used as HTM in CH3 NH3 PbBr3 perovskite solar cells yielding an efficiency of 5.8 %. The reference HTM (Spiro‐OMeTAD), under the same testing conditions, furnished a lower efficiency of 5.1 %. Steady‐state and time‐resolved photoluminescence of the thin films showed good charge‐extraction dynamics for H1 devices. In addition, H1 shows a large thermal stability and completely amorphous behavior (as evaluated by thermal gravimetric analysis and differential scanning calorimetry). Abstract : Efficiency on sale : An oxadiazole‐based π‐spacer is used in a new donor–π–donor structured hole‐transport material for perovskite solar cells. When tested in a device, this compound yields power conversion efficiency values higher than the commonly used reference material. Thanks to the extremely simple synthetic route, this material helps to achieve an important goal in the field of perovskite solar cells: fabrication of high performance devices, while reducing costs.